NEW DESIGN MODIFICATIN OF LOOP AERIAL - O. A. Yurtsev; Y. Y. Bobkov; V. V. Keda (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The work is deal with one new design of loop antenna in which the 4 linear polarizations can be achieved: vertical, horizontal and two oblique polarization with angle 45° to horizontal plane. The numerical simulation results are present in the work.